2018
DOI: 10.3991/ijoe.v14i03.8420
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks and the Mass Appraisal of Real Estate

Abstract: <p>With the rapid development of computer, artificial intelligence and big data technology, artificial neural networks have become one of the most powerful machine learning algorithms. In the practice, most of the applications of artificial neural networks use back propagation neural network and its variation. Besides the back propagation neural network, various neural networks have been developing in order to improve the performance of standard models. Though neural networks are well known method in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…The writers considered exogenous variables and circumstances, such as neighbouring structures and the surrounding area of a home. Zhou et al [22] [25] attempted to develop a forecasting model for real estate evaluation prices using ANN regression and compared the model to ANN and multiple regressions. The study is essential since it tried to forecast a time series index for the African real estate industry using a macroeconomic indicator and machine learning techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The writers considered exogenous variables and circumstances, such as neighbouring structures and the surrounding area of a home. Zhou et al [22] [25] attempted to develop a forecasting model for real estate evaluation prices using ANN regression and compared the model to ANN and multiple regressions. The study is essential since it tried to forecast a time series index for the African real estate industry using a macroeconomic indicator and machine learning techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mass appraisal, also called automatic valuation of real estate assets, is the introduction of mathematical statistics, computer technology, and geographic information technology to establish a mathematical model that serves as a systematic appraisal of a group of real estate properties and reveals its market value (Zhou, Ji, Chen, & Zhang, 2018). The Basel II Accord, issued by the Basel Committee on Banking Supervision (BCBS) in 2008, states that "the bank is expected to monitor the value of the collateral on a frequent basis and at a minimum once every year.…”
Section: Introductionmentioning
confidence: 99%
“…The application of ANN in the mass appraisal of properties has improved the credibility and efficiency of the evaluation system [55]. Unarguably, this area remains a fertile ground for more research activities as revealed by [56].…”
Section: Mass Appraisalmentioning
confidence: 99%